Effect of Salivary Melatonin on Ionizing Radiation Worker and its Effect on Periodontal Disease - Waleed, Shams K.; Mohammed, Ahlam T.; Uthman , Asmaa T. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The use of ionizing radiation, such as radiotherapy and medical imaging, is common in modern medicine. However, it can have negative effects on the body, such as an imbalance in oxidative stress, which can lead to periodontal or gum disease. Radiographers are particularly at risk of experiencing this due to increased levels of reactive oxygen species. Antioxidant therapy, such as melatonin, may help to minimize oxidative stress and protect tissues. Objectives: The this study aimed to evaluate the impact of radiation on periodontal conditions among radiation workers, as well as to assess the levels of melatonin in their bodies. Patients and Methods: The study group consisted of 40 men who had worked with ionizing radiation for 5 years or more, while the control group consisted of 40 men who worked as nurses or lab workers. Unstimulated salivary samples were collected from all subjects to measure salivary melatonin levels. Both groups were then evaluated for the plaque index, bleeding on probing, probing pocket depth, and clinical attachment loss. Results: The results of the study showed that the study group had a higher mean plaque index (1.41 ± 0.484) compared to the control group (1.14±0.524) (p=0.013), a higher mean probing pocket depth (4.40±1.463) compared to the control group (2.82±2.328) (P=0.0002), and a higher mean clinical attachments loss (2.67 ±1.461) compared to the control group (1.59±1.919) (P=0.004). However, there was no significant difference in the mean gingival bleeding between the two groups. Additionally, the study group had a lower mean salivary melatonin level (34.19±13.849) compared to the control group (42.43±16.783) (P=0.013). Conclusion: This study suggests that radiation exposure may increase the risk of periodontal disease. The results also indicate that both radiation and periodontitis can affect salivary melatonin markers, which may be useful in identifying periodontitis.